The failure of the transitional process in Yemen: The Houthi's violent rise to power and the fragmentation of the state - Mareike Transfeld (Stiftung Wissenschaft und Politik (SWP), 2015)
On 22 January 2015 the Yemeni president and government resigned in protest at their own political powerlessness. The transitional process initiated in 2011 has failed. The Houthis, a rebel movement from northern Yemen, reject the federal division of the country as stipulated in the draft constitution of January 2015, and have seized control of state institutions by force of arms. Opposition to the movement is growing, particularly in central and southern Yemen. Meanwhile Al-Qaeda in the Arabian Peninsula (AQAP) risks gaining in strength. Germany and its European partners must urge all parties to the conflict to find a political solution, in an effort to counteract the ongoing fragmentation of the State and prevent further escalation of the violence. (SWP Comments)
Keywords: 320